2021
DOI: 10.3348/kjr.2020.1171
|View full text |Cite
|
Sign up to set email alerts
|

Rare Neurovascular Diseases in Korea: Classification and Related Genetic Variants

Abstract: Rare neurovascular diseases (RNVDs) have not been well-recognized in Korea. They involve the central nervous system and greatly affect the patients' lives. However, these diseases are difficult to diagnose and treat due to their rarity and incurability. We established a list of RNVDs by referring to the previous literature and databases worldwide to better understand the diseases and their current management status. We categorized 68 RNVDs based on their pathophysiology and clinical manifestations and estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 107 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…This may be related to the fact that intracranial atherosclerotic disease and moyamoya disease are also more prevalent in Asians than in Western populations; the reason for this is also unknown [ 22 - 25 ]. The predominance of intracranial artery dissection in certain ethnic groups or children suggests that there may be genetic susceptibilities contributing to the intracranial artery dissection [ 4 , 16 , 26 ]. It has been reported that SCAD may be a complication of monogenic connective tissue diseases, such as vascular Ehlers-Danlos syndrome [ 27 ] and Marfan syndrome [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the fact that intracranial atherosclerotic disease and moyamoya disease are also more prevalent in Asians than in Western populations; the reason for this is also unknown [ 22 - 25 ]. The predominance of intracranial artery dissection in certain ethnic groups or children suggests that there may be genetic susceptibilities contributing to the intracranial artery dissection [ 4 , 16 , 26 ]. It has been reported that SCAD may be a complication of monogenic connective tissue diseases, such as vascular Ehlers-Danlos syndrome [ 27 ] and Marfan syndrome [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] The predominance of intracranial artery dissection in certain ethnic groups or children suggests that there may be genetic susceptibilities contributing to the intracranial artery dissec-tion. 4,16,26 It has been reported that SCAD may be a complication of monogenic connective tissue diseases, such as vascular Ehlers-Danlos syndrome 27 and Marfan syndrome. 28 In addition, some studies have shown that variations in genes such as ICAM-1 29 (intercellular adhesion molecule 1), RNF213 (ring finger protein 213), 30 and MTHFR 31 (methylenetetrahydrofolate reductase) may be associated with SCAD.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases can be caused by deformations in the endothelium layer, smooth muscle layer of blood vessels, and other molecular bases of pathogenesis (Sam et al 2015 ). Apart from strokes, the most common neurovascular diseases are aneurysms, arteriovenous malformations, intracranial dural arteriovenous shunts, and spinal cord arteriovenous shunts, nevertheless, there are many other rarer neurovascular diseases (Song et al 2021 ; van den Berg 2003 ). Most neurological diseases can arise from exposure to environmental chemicals or genetic predisposition (Yirun et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As compared to patients in Western countries, intracranial arterial dissections in Koreans occur most commonly in the posterior circulation, particularly in the vertebral artery (VA) [ 1 , 6 ]. Therefore, there seems to be an ethnic or genetic disposition in the development of VA dissection [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%